MEKANISME DEFORMASI, PERGERAKAN (SENSE SHEAR) DAN PERKEMBANGAN STRUKTUR DALAM PROSES DEFORMASI DUCTILE - Fahrudin Fahrudin (TEKNIK, 2011)
The deformation mechanisme in ductile – transition zone show microfracture cataclasis activities,intracrystalline deformations, twinning, kinking, solid-sate diffusion creep, recovery and recrystallisation. Thatactivities to extend the sense shear indication. Sense shear can see i.e porfiroclast, mica fish, porfiroblast, veins,strain shadow, strain fringe and boudin. Commonly sense shear indications to get the form of ellipsoid geometry.That geometry experience to development the structure along progressive deformations process. Thedevelopment of inclusion and fabric also occur at that process.